The baby book (New York : DK, 2013)
Celebrate the joys of pregnancy and parenthood. The Baby Book presents fascinating facts along side practical advice on all aspects of being a modern parent--from pregnancy and birth to baby and childcare for the first three years, including a specific chapter on having another baby.
Includes index.
Keywords: Infants -- Care -- Handbooks, manuals, etc; Child care -- Handbooks, manuals, etc; Pregnancy -- Handbooks, manuals, etc; Childbirth -- Handbooks, manuals, etc